SEBARAN SPASIAL KASUS GIGITAN HEWAN PENULAR RABIES (GHPR) DI KABUPATEN KOLAKA UTARA - Jumakil, Jumakil; Aswar, Aswar; Rusli Afa, Jusniar; Tina, Lymbran; Fithria, Fithria (Jurnal Spasial, 2025)
There were 111 cases of Rabies Transmitter Animal Bites from January to December 2018 in North Kolaka Regency and 1 positive case of rabies (lyssa), to be precise in Lapai Village. In 2019, another GHPR case was found in North Kolaka Regency. There were 8 cases in February 2019, 22 cases in March 2019 and 1 case tested positive for rabies (lyssa), and 12 cases in April 2019. This type of research is descriptive observational with a spatial approach to determine the distribution of rabies transmitting animal bites in humans based on geographic information systems. The objects in this study were 42 cases of which were recorded in the 2019 KolakaUtara Regency Health Office report and 4 new cases which were found when the study was carried out. The total number of research objects was 46 cases of rabies transmitting animal bites. The results showed that rabies transmitter animal bites cases were spread throughout the Kolaka Utara Regency with the most distribution in Tandaumera Village with 8 cases (17.39%), while the lowest distribution of cases was in Sulaho, Lapai, Watumotoha, Tiwu, Tolala, Lawolatu, Puncak Monapa, Sarambu. , Pohu, Lapasi-pasi, Woise, Patowonua, Tahibua, Lawaki, Lawakara, Latowu each 1 case (0.22%).